Improving Student Competence in The Era of The Industrial Revolution 4.0 Through The MBKM Program - Deasy Arisanty; Ersis Warmansyah Abbas; Syahril Syahril; Karunia Puji Hastuti (Social Studies Education Department, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, 2022)
Improving Student Competence in The Era of The Industrial Revolution 4.0 Through The MBKM Program